2012
DOI: 10.1021/bi2016537
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of the Suicide Protein O6-Alkylguanine-DNA Alkyltransferase for Increased Reactivity Results in an Alkylated Protein with Exceptional Stability

Abstract: Here we present a biophysical, structural, and computational analysis of the directed evolution of the human DNA repair protein O 6 -alkylguanine-DNA alkyltransferase (hAGT) into SNAP-tag, a self-labeling protein tag. Evolution of hAGT led not only to increased protein activity but also to higher stability, especially of the alkylated protein, suggesting that the reactivity of the suicide enzyme can be influenced by stabilizing the product of the irreversible reaction. Whereas wild-type hAGT is rapidly degrade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 38 publications
4
91
0
Order By: Relevance
“…However, cellular alkylated SNAP-tag has been known to resist degradation compared to alkylated-MGMT. 41 Under the same imaging conditions, no obvious fluorescence reduction was observed for the nucleus localized SNAP-H2B proteins alkylated with BG-CCVJ (Fig. 5a, CHO SNAP-H2B).…”
Section: Resultsmentioning
confidence: 82%
“…However, cellular alkylated SNAP-tag has been known to resist degradation compared to alkylated-MGMT. 41 Under the same imaging conditions, no obvious fluorescence reduction was observed for the nucleus localized SNAP-H2B proteins alkylated with BG-CCVJ (Fig. 5a, CHO SNAP-H2B).…”
Section: Resultsmentioning
confidence: 82%
“…However, the K d for immobilized streptavidin is reduced compared with streptavidin in solution (Chivers et al , 2010), so BB primers were adopted in an effort to partially compensate for this loss of affinity (Dressman et al , 2003). In order to capture the POI that was in vitro expressed from the DNA template, the POI was fused with the SNAP-tag (AGT, O 6 -alkylguanine-DNA-alkyltransferase) (Keppler et al , 2003; Mollwitz et al , 2012) that reacts with the BG forming a covalent thioether bond (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The plasmid pIVEX-SNAP-HA was derived from pIVEX-SNAP-GFP (Keppler et al , 2003; Mollwitz et al , 2012) by double digestion with NotI and BamHI and subsequent ligation with T4 DNA ligase (1 h, room temperature) to the overlapping oligonucleotides F-HA and R-HA coding for the HA-tag (Supplementary Table S3). F-HA and R-HA were mixed and incubated with a ramp from 85°C to room temperature to let them anneal, before ligation into the digested vector.…”
Section: Methodsmentioning
confidence: 99%
“…21,26 It has been previously reported that alkylated MGMT is more sensitive to proteases such as trypsin. 27,28 The increased protease susceptibility can be interpreted as a decreased stability of the alkylated protein. Currently, the alkylated-MGMT degradation kinetics can be obtained by detecting alkylated MGMT protein fragments via SDS-PAGE gels.…”
Section: Kinetic Analysis Of Bg-sbd Reaction With Mgmt and Alkylated-mentioning
confidence: 99%